Variações em trajetórias de acumulação de capacidades tecnológicas em nível intra-empresarial: uma análise empírica da VALE S.A. - Piana, Janaina (2016)
This thesis relates to the issue of accumulation of technological capabilities at the firm level, their sources (learning mechanisms) and implications for competitive business performance in natural resources industries in the context of emerging economies. During the past 40 years much progress has been made in research on technological capability accumulation at the level of companies in emerging economies. However, there are still important gaps to be exploited particularly in relation to nature and dynamics of the accumulation of intra-firm technological capabilities paths in the context of natural resources industries, especially in mining. The purpose of the research reported here is to contribute to minimize this gap. In particular, this thesis explores intra-firm variations of technological capabilities accumulation paths, their sources (underlying mechanisms of learning) and some implications that are generated for the competitive performance of the company within the mining industry in Brazil, specifically in the mining company Vale, between 1942 and 2015. To achieve this goal, research is based on the combination of literatures of technological capability accumulation, innovation, learning and industrial development for the construction of the conceptual basis. In parallel, the research draws on a qualitative and inductive research design on primary evidence based on extensive field work. This research design is operated from a single case study in depth at Vale, within three major technology areas: prospecting and mineral exploration, mining and mineral processing. Through the implementation of this strategy, the research found: (1) Paths of technological capabilities accumulation relatively distinct between the three areas of analysis. Specifically: (i) the area of mineral prospecting and exploration there was a technological follower path that achieves global leadership position in innovation and production; (ii) the area of mining also showed up a technological follower path that achieves global leadership position in innovation and production, however, with late accumulation of technological capabilities; and (iii) the area of mineral processing showed an early entrance of a world leader in innovation and production from the creation of a distinct path already mapped by global leaders. The technological capabilities accumulation paths have become similar in 2011 when the three areas presented a world leader in innovation and at the same time demonstrated indications of a stagnation process, which restricts the opportunities to entrance in new technological paths and generation of spillovers. (2) The variations found in the technological capabilities accumulation paths are explained by the way in which different underlying mechanisms of learning were combined and used by the firm. Four combinations of learning mechanisms helped to explain the different directions of technological capabilities accumulation paths in the three areas. (3) The variations in the three technological capabilities accumulation paths generated different implications for competitive performance, specifically in terms of innovative, operational / environmental and spillovers performance. The research findings generate contributions to the understanding of the intra-firm relationship between accumulation of technological capabilities and the underlying learning mechanisms. In addition contribute to the understanding of mining industry as an industry that offers opportunities for significant innovations and can contribute to the diversification of the national industry. So, this industry should get special attention from policy makers and business actions to prevent that firms with high innovative potential deconstruct their innovative capabilities and consequently limit their impact to the technological and economic development in the context of emerging economies.